Project-Based Learning in Bahasa Indonesia Instruction: A Needs Analysis in the Merdeka Curriculum Context - Atika Zikri; Mertiza Fitri Mulyani; Afnita; Tressyalina; Syahrul Ramadhan (JF Publisher, 2026)
Project-Based Learning (PBL) has gained substantial empirical support as an instructional model capable of fostering student engagement, higher-order thinking, and authentic communicative competence, yet its systematic adoption in Bahasa Indonesia instruction at the senior secondary level remains limited. This study conducted a comprehensive needs analysis to map the conditions, gaps, and stakeholder requirements preceding PBL implementation in Bahasa Indonesia classrooms at SMA Pembangunan Padang, West Sumatera, Indonesia. Employing a qualitative descriptive design with a needs analysis framework, data were collected from three Bahasa Indonesia teachers, sixty students from Grades X and XI, and one school principal through in-depth interviews, unstructured classroom observation, a needs analysis questionnaire, and a focus group discussion. Data analysis followed Miles et al.'s interactive model, with trustworthiness established through source and method triangulation. Findings reveal four interconnected dimensions of need: teachers require subject-specific PBL implementation guidance and sustained professional development; students demonstrate strong preferences for contextual, collaborative, and product-oriented learning experiences; the school's infrastructure provides an adequate but improvable baseline; and the existing assessment system is structurally misaligned with the holistic evaluation demands of PBL. These findings collectively indicate that PBL adoption at SMA Pembangunan Padang is motivationally feasible but requires coordinated reform across pedagogy, assessment design, and institutional support. The study contributes a multi-dimensional needs analysis framework applicable to Bahasa Indonesia instruction within the Merdeka Curriculum context.